Deževniki kot kazalniki onesnaženosti tal - Al Sayegh-Petkovšek, Samar (Acta silvae et ligni, 2013)
The metal levels were determined in soil samples in earthworms collected in the vicinity of the abandoned lead smelter (the Upper Meža Valley, Žerjav) andthe largest thermal power plant in Slovenia (the Šalek Valley, Veliki Vrh),near Velenje - Celje road (Črnova) and at the reference area (the Logar Valley, Polanc) with the aim to investigate the transfer of metals from soil to earthworms and to assess the bioindicative potential of earthworms. Our study revealed the following: (i) the highest levels of metals were determinedin earthworms from the most polluted area (Žerjav) and the lowest inearthworms from the reference location (the Logar Valley); (ii) earthworms bioaccumulated Cd, Hg and Zn at all locations, bioaccumulative factors (BCF) of these three metals ranged between 1.18 - 29.2 (Cd), 1.68 - 21.0 (Hg) and 1.10 - 5.57 (Zn), respectively; (iii) earthworms are good bioindicator of polluted soil, since the correlations between Zn, Cd, Cu, Pb, Hg and Mo in soil and in earthworms were established.
Keywords: deževniki; kovine; onesnaženost tal; BCF; biokoncentracijski faktor; bioindikatorji; Slovenia; Slovenija